5 Year Effectiveness Index From Research Ministry Of Marine And Fisheries - Catur Pramono Adi; Pieter Amalo (Universitas Insan Cendekia Mandiri, 2023)
Commodity releases whose index measurement is carried out are released commodities based on the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia number 22/Kepmen-KP/2014 concerning the release of salty tilapia, Kepmen KP Number 77/KEPMEN-KP/2015 regarding the release of pearl catfish, Kepmen KP Number KEP.25/MEN/2006 concerning the release of the Pasupati catfish variety as a superior seed variety. The purpose of measuring the Effectiveness Index of government policies within the BRSDM KP scope is to calculate the effectiveness index of government policies within the BRSDM KP scope through measurement of recommended technologies and commodity releases. The effectiveness index of government policies at the KP Research and Development Agency is calculated based on the policy implications of the Decree of the Minister of Maritime Affairs and Fisheries regarding technology recommendations (rekomtek) and release of technology commodities (release); research results show that, 1). 2016, with an achievement target of 6.5 (effective category); 2). Policy effectiveness categories are measured using a Likert scale with weighted score intervals or weighted indexes; 3) The achievement of the government policy effectiveness index in 2016 was 6.02 in the category of quite effective, with a weighted score of 65.41 which is in the weighted score range of 52.01 - 68.00; or a weighted index of 4.61 - 6.40.